2013
DOI: 10.3126/njog.v7i1.8839
|View full text |Cite
|
Sign up to set email alerts
|

Placenta Accreta: Obstetrician's Nightmare; A Case Series of Seven Patients

Abstract: The incidence of placenta accreta is increasing as a consequence of rising number of cesarean sections and advancing maternal age. A series of seven cases of placenta accreta observed in a short span of four months is being presented. Complication rates in the present series are post partum hemorrhage and major transfusion support (100%), peripartum hysterectomy (100%), ICU admission in four (57%), fever (14%) and bladder injury in one case (14%). Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Also, other investigators reported similar results. In Choudhary et al study all patients were multiparous with 84%, in study by Fitzpatrick et al also, concurrent placenta praevia was recorded in 53% cases, which is lesser compared to 71% in study by Choudhary et al 2 and 64% in study by Fizpatrick et al [10][11][12] According to the current findings, blood transfusion was required in all 166 cases of placenta accreta spectrum. A recent study published in 2018 found that 94.7% of placenta accrete cases required blood transfusion, while another study found that 75.0% cases required blood transfusion.…”
Section: Discussionmentioning
confidence: 43%
“…Also, other investigators reported similar results. In Choudhary et al study all patients were multiparous with 84%, in study by Fitzpatrick et al also, concurrent placenta praevia was recorded in 53% cases, which is lesser compared to 71% in study by Choudhary et al 2 and 64% in study by Fizpatrick et al [10][11][12] According to the current findings, blood transfusion was required in all 166 cases of placenta accreta spectrum. A recent study published in 2018 found that 94.7% of placenta accrete cases required blood transfusion, while another study found that 75.0% cases required blood transfusion.…”
Section: Discussionmentioning
confidence: 43%
“…Present study showed history of previous caesarean section in 76% cases, which highlights the established risk associated with it, in comparison it is 85% in study by Chaudhary D et al 2 Placenta Accreta has an incidence of 1 in 2500 deliveries as per Morgan M et al 5 and 1.7 per 10,000 deliveries as per Fitzpatrick et al 3 . Incidence in this study is 4.3 per 10,000 deliveries.…”
Section: Discussionmentioning
confidence: 80%
“…Also accreta syndromes are one of the leading causes of intractable post partum haemorrhage and emergency peripartum hysterectomy. Recent studies have demonstrated increased incidence of placenta accreta syndrome 2,3 . Anterpartum diagnosis can be made using colour Doppler as early as second trimester.…”
mentioning
confidence: 99%
“…In a case series of seven patients, conservative management in two cases failed and one case required delayed hysterectomy while bleeding continued per vaginally in the other case and it emphasizes to check for PV bleed intraoperatively if the placenta is left in situ. 10 We describe a severe case of placenta percreta, in which the placenta was left in situ during cesarean section and a classical uterine incision was used for extraction of the fetus to avoid the morbidly adherent low placenta with bilateral internal iliac artery ligation. The placenta was left in situ, because spontaneous separation of placenta did not take place.…”
Section: Discussionmentioning
confidence: 99%